Comparative Literature in Classroom: A Model - Singh, Ravindra Pratap (Journal of Applied Cultural Studies, 2015)
Many questions arise in the understanding of texts produced in different locales within the bigger ambit of world literature. It is here that the need arises to apply various modes of enquiry in understanding them. Comparative literature can become a common platform for understanding different cultures and literatures. The present paper is a modest attempt to introduce the concept of comparative literature to a fresh learner and then to evaluate literatures from two different contexts (Dalit and African American) together for practical purposes. A model is proposed for discussing comparative literature in the classroom. Thus, the paper becomes authentic and unique research, bringing theory and practice together.